Efeitos de intervenção psicológica preparatória à cirurgia, no processo de adaptação pós-operatório, em pacientes submetidos à cirurgia ortognática - Santos, Edilaine Dos; Neme, Carmen Maria Bueno [UNESP]; Tavano, Liliam D'aquino (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2000)
This research aimed to verify the effects of relaxation training and cognitive intervention (visualization) introduced in the pre-operatory phase of patients applying to orthognatic surgery. The 12 subjects, of both sexes, between 18 and 26 years of age, were divided into an Experimental Group (E.G./N=6) and a Contral Group (C.G./N=6). After the pre-surgery guidance, both groups were interviewed and the E G. was submitted to relaxation and visualization. During the post-operatory phase all them received psychological attendance and were evaluated in three moments. The results indicated attainment of major benefits in the psycho-organic conditions and others to the EG.. When the psychological interventions are introduced in the pre-operatory, they tend to make the post-operatory phase conditions of the patients better.

Esta pesquisa objetivou verificar os efeitos de treino de relaxamento e intervenção cognitiva (visualização) introduzidos no pré-operatório de pacientes candidatos à cirurgia ortognática. Os 12 sujeitos, de ambos os sexos, entre 18 e 26 anos, foram divididos em Grupo Experimental (G.E./N=6) e Grupo Controle (G.C./N=6). Após a orientação pré-cirúrgica, ambos os grupos foram entrevistados e o G.E. foi submetido ao relaxamento e visualização. No pós-operatório, todos receberam acompanhamento psicológico e foram avaliados em três momentos. Os resultados indicaram obtenção de maiores benefícios nas condições psico-orgânicas e outras para o G.E. As intervenções psicológicas, quando introduzidas no pré-operatório, tendem a melhorar as condições pós-operatórias dos pacientes.
Effects of psychological and preparatory intervention surgery in the process of post operatory adaptation on patients submitted to orthognatic surgery
Keywords: intervenções psicológicas; relaxamento; visualização; pré-operatório e pós- operatório; psychological intervention; relaxation; visualization; preoperatory phase; post-operatory phase